Comparison of Gel Preparation Methods on Gel Strength Measurement of Carrageenan. Issue 1 (March 2021) - Fateha,; Ulya, N; Asmanah,; Agusman,
Abstract: This study aims to develop a carrageenan gel strength test method with an emphasis on the carrageenan gel preparation method for measurement. The gel was prepared by comparing the two heating temperatures (80 °C and 90 °C), heating devices (waterbath and hotplate) and measurement (with container and without container). The results showed that there were no difference between cooking temperatures of 80 °C and 90 °C, but heating at 80°C obtained a lower deviasi standard. The use of hotplate and waterbath were not significantly different resulted in gel strength, but the use of hotplate had a slightly larger variation than waterbath. Measuring the strength of the gel that was still in the crystal container and removed from the container were not significantly different, but measurements with the gel condition were still in the container obtained more accurate test results. Based on the results of this study it can be concluded that the carrageenan gel preparation technique by heating at a temperature of 80 °C using a waterbath or hotplate is the best preparation test method. Meanwhile, the gel does not need to be removed from the container before being measured using a texture analyser. The development of this method can be used as a standard gel preparation method for measuring the strength of carrageenan gel.